2021
DOI: 10.1039/d1ra00615k
|View full text |Cite
|
Sign up to set email alerts
|

Bio-mineralisation, characterization, and stability of calcium carbonate containing organic matter

Abstract: The amorphous calcium carbonate (ACC) or polycrystalline vaterite, which has long-term water stability and thermal stability, can be induced by bacteria. These biogenic CaCO3 are organo-mineral complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 60 publications
1
36
0
Order By: Relevance
“…30 In addition, a neutral pH was shown to drive calcite crystallization, while a higher pH (∼11.5) promoted the formation of vaterite. 31 Moreover, pH was respectively in the range of 8.5–9.0 and lower than 8.5 for the crystallization of vaterite 19,20 and calcite 16 in the biotic experiments. Therefore, the effect of pH value on the polymorphs of calcium carbonate is potentially related to the ratio of CO 3 2− /HCO 3 − , which may affect the structure of prenucleation clusters to crystalline polymorphs.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…30 In addition, a neutral pH was shown to drive calcite crystallization, while a higher pH (∼11.5) promoted the formation of vaterite. 31 Moreover, pH was respectively in the range of 8.5–9.0 and lower than 8.5 for the crystallization of vaterite 19,20 and calcite 16 in the biotic experiments. Therefore, the effect of pH value on the polymorphs of calcium carbonate is potentially related to the ratio of CO 3 2− /HCO 3 − , which may affect the structure of prenucleation clusters to crystalline polymorphs.…”
Section: Discussionmentioning
confidence: 86%
“…4), this is consistent with the results of many studies. 5,[16][17][18][19][20][21] However, there are also inconsistent results in previous studies. For example, Guo et al 22 suggested that shear force does not affect the polymorphs of calcium carbonate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also observed in synthetic vaterite synthesis with the addition of LbL coatings and polymer matrices [ 46 , 83 , 84 ]. Recent findings suggest that bacteria might induce the formation of polymorphs of CaCO 3 serving as templates, and that the carbonic anhydrase, also produced by themselves, plays an essential role in the mineralization of vaterite CaCO 3 [ 85 ]. Bacterially induced CaCO 3 mineralization is thought to be important in a range of processes and the study [ 85 ] indicates that Myxococcus xanthus , a soil bacterium, facilitates the formation of spherical vaterite CaCO 3 .…”
Section: Modification Of Various Surfaces With Vaterite Cacomentioning
confidence: 99%
“…Recent findings suggest that bacteria might induce the formation of polymorphs of CaCO 3 serving as templates, and that the carbonic anhydrase, also produced by themselves, plays an essential role in the mineralization of vaterite CaCO 3 [ 85 ]. Bacterially induced CaCO 3 mineralization is thought to be important in a range of processes and the study [ 85 ] indicates that Myxococcus xanthus , a soil bacterium, facilitates the formation of spherical vaterite CaCO 3 . The production of CO 2 and NH 3 by bacteria, the transformation of NH 3 to NH 4 + , and the presence of OH − , leads to increased basicity, leading to the physiochemical conditions favourable for vaterite precipitation onto the surface of bacteria [ 86 ].…”
Section: Modification Of Various Surfaces With Vaterite Cacomentioning
confidence: 99%